Dynamic Pricing and Commission Strategies in Live-Stream: An Incentive Mechanism Analysis - Tong Wang (Journal of Theoretical and Applied Electronic Commerce Research)
This paper explores optimal strategies for manufacturers, streamers, and retailers in a dual-channel environment, focusing on three commission structures and two power structures. Our analysis identifies steady states where dynamic commissions converge, enhancing profitability and stability for all parties. We find that less dominant partners prefer commission structures that reinforce existing power structures. Profitability is influenced by dynamic commissions: under manufacturer dominance, dynamic wholesale price and commission rate increase profitability for manufacturers and retailers while decreasing streamers’ profits. In contrast, under streamer dominance, a dynamic commission rate enhances streamers’ profits but reduces those of manufacturers and retailers. This evaluation highlights the shared interests between manufacturers and retailers. Taking the spillover effect into account, commission strategies should consider hassle cost, initial commission rate, and spillover impact. Product selection strategies show consistent trends, with moderate hassle cost and a disutility factor ranging from moderate to high, regardless of the spillover effect.